Analisis Kepuasan Pengguna SIAKAD Menggunakan Metode End User Computing Satisfaction (EUCS) dan Importance Performance Analysis (IPA) - Juan Muhamad Faqih; Goldie Gunadi (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The Academic Information System (SIAKAD) is a crucial digital infrastructure in managing higher education academic services, but its effectiveness is often hampered by low user satisfaction due to a system design that is less responsive to real needs. This study aims to analyze the level of SIAKAD user satisfaction at the Faculty of Technology, Widuri Institute of Technology (ISTEK Widuri) and identify system improvement priorities based on the perspective of students as the primary users. The study uses a quantitative approach with the End User Computing Satisfaction (EUCS) method to measure satisfaction in the dimensions of content, accuracy, format, ease of use, and timeliness, and Importance Performance Analysis (IPA) to map the gap between the level of importance and actual system performance. Data were collected through a questionnaire involving 35 student respondents and analyzed using SPSS. The results show that the accuracy and timeliness dimensions received the highest ratings, while the content and ease of use dimensions still require significant improvement. The IPA analysis identified several attributes in Quadrant II as top priorities for improvement because they have a high level of importance but low performance. This study concludes that the integration of EUCS and IPA is effective as an evaluation framework for academic information systems and can be a strategic basis for institutions in developing SIAKAD that is more responsive, accurate, and user-oriented.